Selective laser melting of yttria-stabilized zirconia. (26th October 2018) - Guan, Jieren; Wang, Qiuping; Zhang, Xiaowei; Jiang, Yehua; Yan, Yongnian; Xiao, Jingyu; Ren, Bo
Abstract: The mechanism of phase transformation and microstructure of yttria-stabilized zirconia (YSZ), prepared by selective laser melting (SLM) at a laser wavelength of 1 μ m, has been investigated. Also, the effect of different working gases and heat treatment has been studied. Experimental results present that processing parameters can be optimized and determined by Liner Energy Density. X-ray diffraction analysis confirmed the absence of monoclinic phase under argon flow during SLM, with gray-color appearance due to the lack of oxygen, which impedes the transformation from tetragonal to monoclinic phase partially. Later, the color becomes white during heat treatment because samples are exposed to the air with sufficient amount of the oxygen and the diffraction peaks of monoclinic phase increased. When SLM and heat treatment was carried out in the air, the YSZ samples appeared in white-color, which indicates the presence of both monoclinic and tetragonal phase. The morphology and microstructure showed there occurred bonding phenomenons among particles, only surface partially melted between particles with weak bonding strength. The top surface morphology of air-prepared sample showed cracks, un-melting particles and cave-like pores because of uneven distribution of temperature variations. This paper also made a preliminary research and provided a feasibility method to melt zirconia ceramics completely, in which more energy input by multi-scanning in the air working gas.